Increasing the Potential, Interest, and Self-Awareness of High School Students Entering College Through the Faculty Fair KKN-PPM UGM Program - Wulandari, Cahyo; Prasetyaningrum, Heni; Firdausa, Salma Salsabila (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Recognizing interests and potential is sometimes still difficult for some teenagers. They will do a lot of exploration to find out their interests and potential. However, many of them still have difficulty in going through the process, including teenagers who want to continue to higher education. Confusion in choosing a study program, lack of information related to college life and the types of scholarships offered are problems that they often experience. To facilitate these needs, a series of activities were carried out to introduce various study programs at Universitas Gadjah Mada through the KKN-PPM UGM faculty fair program. This activity is expected to help students increase their interest and self-awareness to prepare themselves to enter higher education. The method of implementing this activity is interviews, socialization using the Johari Window and SWOT and socialization through a faculty fair held at SMAN 1 Wedung, Wedung District, Demak Regency, Central Java. In addition to socialization, students were also given pre-test and post-test questionnaires to determine the conditions before and after the activity was held. This study uses a descriptive quantitative approach by comparing the answers to the questionnaires to determine the impact of the activities that have been carried out. The results of this activity showed an increase in the percentage of ’agree’ and ’strongly agree’ answers to the pre-test and post-test questions by 14% in the aspect of understanding related to study programs and 23% related to college entrance pathways, an increase of 36% related to college life, 24% related to scholarships available at college, an increase of 7% in plans after graduating from school and 30% in the picture related to the future. Therefore, it can be concluded that this program is able to improve students’ understanding of future plans, their knowledge and interest in continuing their education to a higher level.